Hail climatology and its possible attributions in Beijing, China: 1980-2021 - Bian, Yuxuan; Hu, Yaqiong; Li, Mingxin; Li, Jianying; Huang, Mengyu; Ma, Xincheng (Frontiers in Environmental Science, 2023)
Hail hazards have caused severe losses and threatened the safety of residents in Beijing, the Chinese capital city. A refined analysis of the spatial and temporal distribution of hailstorms in Beijing can help to evaluate the risk of hail and guide the operations of hail prevention. The distribution of weather stations is relatively sparse to figure out the fine distribution of hail events. Therefore, a quality-controlled dataset of disaster information data reported from information reporters is used to analyze the fine temporal and spatial distributions of hail days and events in Beijing from 1980 to 2021 in this study. Hail events and hail days show an obvious downward trend with years from 1981 to 2010, while hail events show a strong upward trend from 2011 to 2021. The seasonal pattern of hail events shows a unimodal distribution from March to October, and the peak appears in June. Most of the hail events occurred from 14:00 to 21:00, while the highest counts appeared from 15:00 to 17:00. More and larger hails occurred in the northwestern mountains rather than southeastern plains in Beijing, highly correlated with the topography. Both total and severe hails hit the mountain area statistically earlier than the plain area. The most frequent hours of hails in the northwestern area and southeastern area were concentrated in the range of 13:00—17:00 and 16:00—20:00 CST, respectively. This time delay is due to the initiation location and movement direction of the convective storms. The influence of ENSO on warm season hails is positive in Beijing, which has a lag of 3 months or longer. The arctic oscillation has a negative correlation with hail days in each month from May to September.